2017
DOI: 10.7554/elife.26969
|View full text |Cite
|
Sign up to set email alerts
|

Rv3723/LucA coordinates fatty acid and cholesterol uptake in Mycobacterium tuberculosis

Abstract: Pathogenic bacteria have evolved highly specialized systems to extract essential nutrients from their hosts. Mycobacterium tuberculosis (Mtb) scavenges lipids (cholesterol and fatty acids) to maintain infections in mammals but mechanisms and proteins responsible for the import of fatty acids in Mtb were previously unknown. Here, we identify and determine that the previously uncharacterized protein Rv3723/LucA, functions to integrate cholesterol and fatty acid uptake in Mtb. Rv3723/LucA interacts with subunits … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
191
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(202 citation statements)
references
References 70 publications
11
191
0
Order By: Relevance
“…These data are supportive of the conclusion that the mce6 genes are repressed in a whiB6-dependent manner, although further characterization studies will be required to support this hypothesis. mce genes have been associated with carbon nutrient uptake, including mce1, promoting uptake of fatty acids (88), and mce4, promoting uptake of cholesterol (89). mce6 is absent in the M. tuberculosis genome but is present in the genomes of many nontuberculous mycobacterial species (90) and could play a role in controlling metabolite import to promote survival in the phagosome or cytosol.…”
Section: Figmentioning
confidence: 99%
“…These data are supportive of the conclusion that the mce6 genes are repressed in a whiB6-dependent manner, although further characterization studies will be required to support this hypothesis. mce genes have been associated with carbon nutrient uptake, including mce1, promoting uptake of fatty acids (88), and mce4, promoting uptake of cholesterol (89). mce6 is absent in the M. tuberculosis genome but is present in the genomes of many nontuberculous mycobacterial species (90) and could play a role in controlling metabolite import to promote survival in the phagosome or cytosol.…”
Section: Figmentioning
confidence: 99%
“…M. tuberculosis imports fatty acids from host triglycerides for synthesis of its own lipid inclusions and acquisition of dormancy traits in macrophages ( 46 , 47 ). The mycobacterial protein, LucA, was found to form a complex with Mce1 and Mce4 fatty acid transporters to facilitate cholesterol and fatty acid uptake in infected macrophages ( 48 ). In dormant M. tuberculosis , the accumulation of triglycerides is modulated by fatty acid CoA ligase 6 ( 49 ), and during nutrient starvation, the bacterium is capable of hydrolyzing these stored triglycerides, owing to its lipase activity ( 50 ).…”
Section: Host Lipids—the Protagonist and The Antagonist In The Macropmentioning
confidence: 99%
“…Recent work has shown that Dicl1 'bypass' mutants, which either alleviate methylcitrate toxicity or reduce the catabolic flux of propionyl-CoA, are able to rescue the growth defect by alleviating the accumulation of toxic metabolites. This led to the identification of a previously uncharacterized protein, Rv3723/LucA, which functions to integrate cholesterol and fatty acid uptake in M. tuberculosis [55]. Similar experiments in other key pathogens will likely uncover more uncharacterized proteins dedicated to propionate metabolism and/or alleviating toxicity.…”
Section: Mycobacteriamentioning
confidence: 99%